2020
DOI: 10.1016/j.jphotochem.2020.112833
|View full text |Cite
|
Sign up to set email alerts
|

Singlet oxygen generation by porphyrins and metalloporphyrins revisited: A quantitative structure-property relationship (QSPR) study

Abstract: Porphyrins and metalloporphyrins are used as photosensitizers in photocatalysis, photodynamic therapy (PDT), disinfection, degradation of persistent pollutants and other applications. Their mechanism of action involves intersystem crossing to triplet excited state followed by formation of singlet oxygen (1 O2), which is a highly reactive species and mediates various oxidative processes. The design of advanced sensitizers based on porphyrin compounds have attracted significant attention in recent years. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…From Figure S8 and Figure S9, the generation of • OH and • O 2 − is negligible in all groups, suggesting that the sonodynamic mechanism of HNTM-Pt@ Au was similar to that of the type II PDT. 39,40 As shown in Figure 2F, the sonocatalytic mechanism can be summarized as the following two points: (i) Au NRs can enhance the ultrasonic cavitation and improve the absorption of ultrasonic energy in the system; (ii) Au NRs and Pt single atoms acted as electron acceptors to promote the transfer of electrons generated from HNTM, improving the separation efficiency of electron−hole pairs. Sonocatalytic Activity of Different Metal Single Atoms and Theoretical Calculations.…”
Section: Resultsmentioning
confidence: 99%
“…From Figure S8 and Figure S9, the generation of • OH and • O 2 − is negligible in all groups, suggesting that the sonodynamic mechanism of HNTM-Pt@ Au was similar to that of the type II PDT. 39,40 As shown in Figure 2F, the sonocatalytic mechanism can be summarized as the following two points: (i) Au NRs can enhance the ultrasonic cavitation and improve the absorption of ultrasonic energy in the system; (ii) Au NRs and Pt single atoms acted as electron acceptors to promote the transfer of electrons generated from HNTM, improving the separation efficiency of electron−hole pairs. Sonocatalytic Activity of Different Metal Single Atoms and Theoretical Calculations.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, models reported for pteridines, furicoumarins and porphyrins showed RMS Φ Δ errors of 5.7–24.8 %. [ 47 , 48 , 49 ] It should be noted that in these studies the values of singlet oxygen quantum yields were measured in identical conditions for all compounds in the dataset. In the current study we used larger datasets (>40 BODIPYs for each model) with Φ Δ values measured using different 1 O 2 traps and reference photosensitizers.…”
Section: Resultsmentioning
confidence: 99%
“… [46] However, earlier we showed that QSPR may be used for the analysis of 1 O 2 production by pterins and flavins, [47] psoralens and angelicins, [48] porphyrins and metalloporphyrins. [49] In this regard, applying QSPR for the prediction of Φ Δ values for heavy‐atom‐free BODIPYs in solvents of different polarity offers a means to estimate SOCT‐ISC efficiency in these systems. Hence, we started to search BODIPY structures which undergo SOCT‐ISC to correlate molecular features to singlet oxygen quantum yields with the aid of machine learning methods.…”
Section: Introductionmentioning
confidence: 99%
“…46 However, earlier we showed that QSPR may be used for the analysis of 1 O 2 production by pterins and flavins, 47 psoralens and angelicins, 48 porphyrins and metalloporphyrins. 49 In this regard, applying QSPR for the prediction of  Δ values for heavy-atom-free BODIPYs in solvents of different polarity offers a means to estimate SOCT-ISC efficiency in these systems. Hence, we started to search BODIPY structures which undergo SOCT-ISC to correlate molecular features to singlet oxygen quantum yields with the aid of machine learning methods.…”
Section: Introductionmentioning
confidence: 99%